Contractility of isolated colonic smooth muscle strips from rats treated with cancer chemotherapy: differential effects of cisplatin and vincristine - López-Tofiño, Yolanda; Barragán del Caz, Luis Felipe; Benítez-Álvarez, David; Molero-Mateo, Paula; Nurgali, Kulmira; Vera, Gema; Bagües, Ana; Abalo, Raquel (Frontiers in Neuroscience, 2023)
Background: Certain antineoplastic drugs cause gastrointestinal disorders even after the end of treatment. Enteric neuropathy has been associated with some of these alterations. Our goal was to assess the impact of repeated treatment with cisplatin and vincristine on the contractility of circular and longitudinal muscle strips isolated from the rat colon. Methods: Two cohorts of male rats were used: in cohort 1, rats received one intraperitoneal (ip) injection of saline or cisplatin (2 mg kg −1 week −1 ) on the first day of weeks 1-5; in cohort 2, rats received two cycles of five daily ip injections (Monday to Friday, weeks 1-2) of saline or vincristine (0.1 mg kg −1 day −1 ). Body weight and food and water intake were monitored throughout the study. One week after treatment, responses of colonic smooth muscle strips to acetylcholine (10 -9 -10 -5 M) and electrical field stimulation (EFS, 0.1-20 Hz), before and after atropine (10 -6 M), were evaluated in an organ bath. Results: Both drugs decreased body weight gain. Compared to saline, cisplatin significantly decreased responses of both longitudinal and circular smooth muscle strips to EFS, whereas vincristine tended to increase them, although in a non-significant manner. No differences were observed in the muscle response to acetylcholine. Atropine abolished the contractile responses induced by acetylcholine, although those induced by EFS were only partially reduced in the presence of atropine. Conclusions: The findings suggest that although both drugs cause the development of enteric neuropathy, this seems to have a functional impact only in cisplatin-treated animals. Understanding the effects of chemotherapy on gastrointestinal motor function is vital for enhancing the quality of life of cancer patients.